Digital information ecosystems : smart press - Dominique, Augey; Alcaraz, Marina (Chichester Wiley, 2019)
Digital information, particularly for online newsgathering and reporting, is an industry fraught with uncertainty and rapid innovation. Digital Information Ecosystems: Smart Press crosses academic knowledge with research by media groups to understand this evolution and analyze the future of the sector, including the imminent employment of bots and artificial intelligence
Keywords: Digital libraries; Electronic information resources